2017
DOI: 10.1016/j.ygyno.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of progression free survival and overall survival of ovarian cancer patients with clear cell carcinoma versus serous carcinoma treated with platinum therapy: An NRG Oncology/Gynecologic Oncology Group experience

Abstract: Purpose We examined disparities in prognosis between patients with ovarian clear cell carcinoma (OCCC) and serous epithelial ovarian cancer (SOC). Methods We reviewed data from FIGO stage I–IV epithelial ovarian cancer patients who participated in 12 prospective randomized GOG protocols. Proportional hazards models were used to compare progression-free survival (PFS) and overall survival (OS) by cell type (clear cell versus serous). Results There were 10,803 patients enrolled, 9,531 were eligible, evaluabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 23 publications
3
72
1
Order By: Relevance
“…However, it has significant poorer prognosis in advanced stage. Progression-free survival rate and survival rate in early-stage (I, II) OCCC at 5-year were 75% and 80%, respectively, compared to 63% and 78% in serous carcinoma [22]. In the present study, relapse-free survival rate and OS rate at 5-year for stage I and II were 68% and 91%, respectively, showing good prognosis of early-stage OCCC.…”
Section: Discussionsupporting
confidence: 47%
“…However, it has significant poorer prognosis in advanced stage. Progression-free survival rate and survival rate in early-stage (I, II) OCCC at 5-year were 75% and 80%, respectively, compared to 63% and 78% in serous carcinoma [22]. In the present study, relapse-free survival rate and OS rate at 5-year for stage I and II were 68% and 91%, respectively, showing good prognosis of early-stage OCCC.…”
Section: Discussionsupporting
confidence: 47%
“…However it has significant poorer prognosis in advanced stage. Progression-free survival rate and survival rate in early stage (I, II) OCCC at 5-year were 75% and 80%, respectively, compared to 63% and 78% in serous carcinoma [22]. In the present study, relapsefree survival rate and overall survival rate at 5-year for stage I and II were 68% and 91%, respectively, showing good prognosis of early stage OCCC.…”
Section: Discussionsupporting
confidence: 46%
“…Oliver et al [22] reported that OCCC in early stage has better prognosis than serous carcinoma. However it has significant poorer prognosis in advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, CCCs are typically diagnosed at an early stage; however, they are less responsive to front-line platinum-based chemotherapy, especially at later FIGO stages. When compared to matched serous disease, early stage CCC (I-II) had a better overall survival than serous, but late stage CCC (III-IV) had a worse prognosis than both serous [138] and endometrioid adenocarcinoma [137]. Interestingly, some evidence suggests that drug response can be correlated to CD44-10v isoform expression [139].…”
Section: Ovarian Clear Cell Carcinomamentioning
confidence: 99%